2016
DOI: 10.1016/j.athoracsur.2016.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Liver in the Right Atrium: A Rare Cause of Syncope

Abstract: This report highlights the first case of complete resection of an accessory liver found embedded in the right atrium obstructing venous return to the heart, acutely reducing cardiac output, and producing recurrent syncopal episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…8 There was modest female preponderance in this population (female, 67% 2,6,7,9 ; male, 33% 5,8 ). Forest et al 8 reported the largest AHL with a maximum diameter of 3 cm. At a maximum diameter of 4 cm, the case described herein represents the largest AHL reported to date.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…8 There was modest female preponderance in this population (female, 67% 2,6,7,9 ; male, 33% 5,8 ). Forest et al 8 reported the largest AHL with a maximum diameter of 3 cm. At a maximum diameter of 4 cm, the case described herein represents the largest AHL reported to date.…”
Section: Discussionmentioning
confidence: 75%
“…There are only six other reported cases of this particular type of AHL. 2,[5][6][7][8][9] Patient ages have ranged from 12 years 5 to 69 years. 8 There was modest female preponderance in this population (female, 67% 2,6,7,9 ; male, 33% 5,8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of them, AHT was accidentally found in the RA mimicking the clinical course of atrial myxoma. [2][3][4][5] There is no uniform theory explaining the incidence of AHT within the heart chambers. Clearly, there has to be a hematogenous spread of hepatic cells with regenerative potential to the heart chambers, and in the absence of trauma, the embryological explanation of this phenomenon is the most attractive.…”
mentioning
confidence: 99%
“…A similar approach with the use of DHCA for the resection of AHL has been reported by Forest and colleagues. 4 Use of DHCA seems to be a logical and valuable option providing a blood-free surgical field in the area of the RA-IVC junction, which helps to delineate the entire anatomy of the AHL. On the other hand, femoral cannulation, with the IVC cannula positioned just inferior to the retro-hepatic IVC, may provide sufficient IVC drainage to accomplish AHL resection without DHCA.…”
mentioning
confidence: 99%